Creation and validation of a visual educational technology content for lactation physiology learning - Polyana de Lima Ribeiro; Daiani Oliveira Cherubim; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to create and validate a visual educational technology content for lactation physiology learning. Method: a methodological study that contemplated the stages of content creation and validation guided by the conceptual model of Knowledge Translation into action. The creation took place in partnership with the educational technology center of the project's home institution. The validation was attended by 27 judges with experience in the obstetric, neonatal, pediatric or maternal and child areas and in the theme of breastfeeding. Results: an educational technology covered animation and video techniques to locate, respectively, elements of lactation physiology and the population involved. An Overall Content Validity Index of 0.84 was obtained. Conclusion: the visual educational technology for lactation physiology learning has been validated in content as a tool to introduce the theme and mediate health education actions that can have a positive impact on breastfeeding.